2016
DOI: 10.1371/journal.pone.0147979
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Topical Treatment for Psoriasis Targeting RORγ: From Bench to Skin

Abstract: BackgroundPsoriasis is a chronic inflammatory skin disorder involving marked immunological changes. IL-17-targeting biologics have been successful in reducing the disease burden of psoriasis patients with moderate-to-severe disease. Unfortunately, the stratum corneum prevents penetration of large molecule weight proteins, including monoclonal antibodies. Thus, for the majority of psoriasis patients ineligible for systemic treatments, a small molecule targeting RORγt, the master regulator of IL-17 family cytoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
84
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 70 publications
(85 citation statements)
references
References 39 publications
(39 reference statements)
1
84
0
Order By: Relevance
“…Evidence has accumulated demonstrating that RORs act as ligand-dependent transcription factors [74, 7678]. Cholesterol and cholesterol sulfate and small molecules can interact with the LBD of RORs to modulate their transcriptional activities [79].…”
Section: Rors (Retinoic Acid-related Orphan Receptors) An Overviewmentioning
confidence: 99%
“…Evidence has accumulated demonstrating that RORs act as ligand-dependent transcription factors [74, 7678]. Cholesterol and cholesterol sulfate and small molecules can interact with the LBD of RORs to modulate their transcriptional activities [79].…”
Section: Rors (Retinoic Acid-related Orphan Receptors) An Overviewmentioning
confidence: 99%
“…However, drug delivery to the target site is unconfirmed. Although preclinical biological effects were observed within the time frame studied, a longer treatment period and/or a more frequent application may be needed to induce detectable clinical/biological effects in patients.…”
mentioning
confidence: 99%
“…GSK2981278 is a highly potent and selective inverse agonist of RORγ under development for the topical treatment of psoriasis. Preclinical data showed that GSK2981278 significantly inhibited production of the Th17 signature cytokines in multiple in vitro and human tissue‐based systems . GSK2981278 may block the transcriptional activity of RORγt, leading to local suppression of cytokine expression and ultimately, improvement in psoriasis.…”
mentioning
confidence: 99%
“…A small molecule like Metadichol as alternative topical medicine with biologic like efficacy targets RORγt, the master regulator of IL-17 family cytokines, thus leads to improved clinical outcomes desired in Psoriasis patients. Recent data suggest that topical treatment limits Th17-type cytokine expression with clinical candidates like GSK2981278 could lead to improved health outcomes for patients [35].…”
Section: Metadichol Inverse Agonist Activity Against Ror Gammamentioning
confidence: 99%